Effective Internal Audits Cut Fraud in Indonesia: Audit Internal yang Efektif Memangkas Kecurangan di Indonesia - Cindy Andriana Puspitasari; Dina Dwi Oktavia Rini (Academia Open, 2024)
This study investigates the effectiveness of internal audits in managing regional property fraud tendencies in Prigen District, Pasuruan Regency over five years. Utilizing qualitative methods, data was collected through interviews, observations, and documentation, and analyzed using Nvivo software. Despite the Pasuruan Regency Government consistently achieving "Fair Without Exception" ratings, this research focuses on Prigen District to confirm minimal fraud in regional property. The findings indicate that the fraud triangle theory positively affects fraud tendencies, and internal control plays a crucial role in mitigating these tendencies. The research underscores the importance of robust internal audit practices to reduce fraud in regional property management. Highlight: Internal control is crucial in reducing fraud tendencies. The fraud triangle theory explains fraud tendencies. Robust audit practices are essential for property management. Keywoard: Internal audit, fraud management, regional property, qualitative research, Pasuruan Regency.